Taphonomy of small mammal bone accumulations generated by the Chaco owl (Strix chacoensis, Strigiformes) from the Monte Desert (Mendoza, Argentina): a contribution to South American archaeological and palaeontological studies - López, José Manuel (2018)
The present study analyses the taphonomic features of recent small mammal bone and teeth accumulations recovered from pellets generated by Strix chacoensis in a Natural Protected Area in the central Monte Desert of Mendoza, Argentina. In order to identify the taphonomic signature of this predator in the formation of zooarchaeological and palaeontological accumulations, taxonomic profiles, relative abundances, bone breakage patterns and digestive corrosion were evaluated. Taphonomic results locate S. chacoensis in modification category 2 (intermediate). Although the general taphonomic patterns detected in the present study were similar to a typical owl pattern, some differences from that pattern were detected. This sample showed lesser relative abundances of skeletal elements, greater loss of teeth and a larger number of incisors modified by digestion than those generated by other strigiforms. The comparison with reported archaeological accumulations suggested that the small mammal remains recovered in some sites from the Monte Desert may correspond to the predatory activity of S. chacoensis. The identification of the action of S. chacoensis in archaeological and palaeontological small mammal bone and teeth accumulations is a promising tool to evaluate the conservation status of native forests in the past.